Muslims, Christians, and Jesus : gaining understandings and building relationships - Medearis, Carl. (Minneapolis, Minn. : Bethany House, 2008)
"A guide to gaining understanding and building connections between the world's two largest religions, written from the perspective of a Christian who has lived and worked in Islamic countries"--Provided by publisher.
Introduction -- Before the pillars: the foundations of Islam -- The teachings of Islam: the articles and pillars of faith -- Islam's holy book: the words of God -- Women and Islam: protecting the purity of women -- Common questions: a knowledgeable response -- Jesus meets jihad: overcoming fear with love -- Standing on the bridge: Muslims who follow Jesus -- Love your neighbor: practical ways to reach out to Muslims -- Appendix: statistics and glossary of terms.
Keywords: Christianity and other religions -- Islam; Islam -- Relations -- Christianity; Islam -- Doctrines